POLICY BRIEF: TACKLING THE SOCIAL, ECONOMIC, AND LEGAL IMPACTS OF ONLINE GAMBLING IN INDONESIA - Akbar, Gugun Geusan; Ulumudin, Aceng; Kania, Ikeu; Nurliawati, Nita (Transpublika Publisher, 2024)
Online gambling has rapidly become a pervasive issue in Indonesia, fueled by increased internet access and the widespread use of smartphones. This policy brief provides a comprehensive analysis of the social, economic, and legal impacts of online gambling in Indonesia, while offering actionable policy recommendations to mitigate its negative effects. This research synthesizes findings from six key studies and integrates insights from thematic analysis conducted through stakeholder interviews, including perspectives from psychologists, legal experts, law enforcement officials, and community leaders. The analysis highlights significant mental health challenges associated with online gambling, particularly among teenagers and family leaders, such as increased stress, anxiety, and family disintegration. Economically, online gambling leads to financial ruin for many families, resulting in debt accumulation, loss of assets, and broader community-level economic instability. Legally, the study identifies critical gaps in Indonesia's regulatory framework, which struggles to address the complexities of online gambling in the digital era. The findings underscore the need for comprehensive policy interventions, including updates to legal frameworks, enhanced law enforcement capabilities, public education initiatives, and community-based support systems. By implementing these strategies, Indonesia can more effectively combat the negative impacts of online gambling, protect vulnerable populations, and promote a healthier, more secure society.